The Longest Night : Polemics and Perspectives on Election 2000 - Rosenfeld, Michel, 1948-; Jacobson, Arthur J. (Book collections on Project MUSE., 2002)
The American presidential election of 2000 was perhaps the most remarkable, and in many ways the most unsettling, that the country has yet experienced. The millennial election raised fundamental questions not only about American democracy, but also about the nation's constitution and about the legitimate role of American courts, state and federal, and in particular about the United States Supreme Court.